Networked Reception: Mapping the Anti-Online Gambling Discourse on Ferry Irwandi’s Youtube Channel - Aulia Rahmat; Muhammad Qadaruddin; Irnawati Bachtiar; Reynaldi Reynaldi (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2026)
This study aims to analyze public responses to Ferry Irwandi’s YouTube video criticizing influencers who promote online gambling, using Stuart Hall’s encoding/decoding theory and Social Network Analysis. The research data consist of 5,380 user comments collected from the video’s comment section, which serve as the object of analysis. A quantiCtative approach was applied through network analysis using Gephi to examine interaction patterns and actor centrality, complemented by qualitative content analysis to categorize audience readings into dominant, negotiated, and oppositional positions. The findings indicate that public responses are predominantly characterized by dominant–hegemonic readings, reflecting broad acceptance of the moral critique against online gambling promotion. Negotiated readings appear in the form of partial agreement combined with structural or economic considerations, while oppositional readings remain limited and peripheral within the network. The discussion demonstrates that audience interpretation is not only shaped by individual meaning-making processes but also by the hierarchical structure of online interaction networks, where highly central actors play a significant role in reinforcing dominant meanings. This study concludes that public opinion in digital spaces is formed through the interaction between encoded messages and networked social dynamics. However, the research is limited to a single case and platform, suggesting the need for future comparative and multi-platform studies.